2022
DOI: 10.3389/fnut.2022.999581
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the physiochemical and sensory quality of yogurt by incorporating polyphenol-enriched citrus pomaces with antioxidant, antimicrobial, and antitumor activities

Abstract: Industrial pomaces are cheap sources of phenolic compounds and fibers but dumping them in landfills has negative environmental and health consequences. Therefore, valorizing these wastes in the food industry as additives significantly enhances the final product. In this study, the citrus pomaces, orange pomace (OP), mandarin pomace (MP), and lemon pomace (LP) were collected by a juice company and subjected to producing polyphenols and fiber-enriched fractions, which are included in functional yogurt; the pomac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…The level of polyphenolic compounds found in products with or without cereals is similar to the results obtained by Arafoui et al [ 53 ] which reported a level of 8.5 mg GAE/100 g product in the yogurt formulated as a control. Other authors formulated yogurts with a high content of polyphenolic compounds by adding some subproducts which resulted after squeezing citrus fruits, strawberries, mulberry, dragon fruit, or passiflora [ 54 , 55 , 56 , 57 , 58 , 59 ]. In this case, the concentration of polyphenolic compounds ranged between 0.56 mgGAE/g and 1.28 mgGAE/g for yogurts with citrus [ 54 ] and between 20 mgGAE/mL and 64.43 mgGAE/mL for yogurt formulated with dragon fruit [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of polyphenolic compounds found in products with or without cereals is similar to the results obtained by Arafoui et al [ 53 ] which reported a level of 8.5 mg GAE/100 g product in the yogurt formulated as a control. Other authors formulated yogurts with a high content of polyphenolic compounds by adding some subproducts which resulted after squeezing citrus fruits, strawberries, mulberry, dragon fruit, or passiflora [ 54 , 55 , 56 , 57 , 58 , 59 ]. In this case, the concentration of polyphenolic compounds ranged between 0.56 mgGAE/g and 1.28 mgGAE/g for yogurts with citrus [ 54 ] and between 20 mgGAE/mL and 64.43 mgGAE/mL for yogurt formulated with dragon fruit [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors formulated yogurts with a high content of polyphenolic compounds by adding some subproducts which resulted after squeezing citrus fruits, strawberries, mulberry, dragon fruit, or passiflora [ 54 , 55 , 56 , 57 , 58 , 59 ]. In this case, the concentration of polyphenolic compounds ranged between 0.56 mgGAE/g and 1.28 mgGAE/g for yogurts with citrus [ 54 ] and between 20 mgGAE/mL and 64.43 mgGAE/mL for yogurt formulated with dragon fruit [ 55 ]. In this last case, it is important to mention that the yogurt formulated with dragon fruit used probiotic bacteria supplied by Cristian Hansen [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the peels of citrus fruits, particularly oranges, have higher phenolic content compared to the edible portions, containing compounds like hesperidin. The water extracts of citrus pomace also have significant phenolic and flavonoid content [ 21 ], with high contents of hesperetin-7- O -rutinoside, quercetin, peonidin, and apigenin [ 20 , 21 , 22 , 23 ].…”
Section: Composition In Phenolic Compounds Of By-productsmentioning
confidence: 99%
“… Species Phenolic Compounds Concentration (mg g −1 DW) References Artichoke Apigenin, Caffeic acid , Caffeoylquinic acid, Chlorogenic acid, Coumaric acid, Cynarin, Ferulic acid , Luteolin, Naringenin, Narirutin, Quinic acid 1.99–27.21 [ 8 , 10 , 11 , 12 ] Broccoli Caffeic acid , Chlorogenic acid, Coumaroylquinic acid, Ferulic acid , Kaempferol, Quercetin , Sinapic acid 6.70–163.18 [ 14 , 16 , 18 , 19 ] Cauliflower Caffeic acid , Coumaric acid, Ferulic acid , Kaempferol, Lutein, Quercetin , Sinapic acid 3.45–10.70 [ 17 , 40 , 41 ] Citrus sp. Apigenin, Benzoic acid, Caffeic acid, Caffeine, Caffeoylquinic acid, Caffeoyltartaric acid, Catechol, Catechin , Chlorogenic acid, Cinnamic acid, Cyanidin, Delphinidin, Dihydroxyflavone, Diosmin, Ellagic acid, Eriocitrin, Eriodictyol, Ferulic acid, Gallic acid , Gentisic acid, Hesperetin, Isorhamnetin, Isosakuranetin, Kaempferol, Luteolin, Malvidin, Myricetin, Naringenin, Naringin, Narirutin, Neoeriocitrin, Neohesperidin, 4-hydroxybenzoic acid, Pelargonidin, Peonidin, Phloretin, Propylgallate, Quercetin , Resveratrol , Rosmarinic acid , Rutin, Scopoletin, Sinapic acid, Sinensetin, Syringic acid, Vanillin, Vanillic acid, Vitexin 3.00–196.20 [ 20 , 21 , 22 , 23 , …”
Section: Composition In Phenolic Compounds Of By-productsmentioning
confidence: 99%
“…Ten grams from each medicinal plant's powder was extracted with 200 mL of 80% methanol for 1 h in an ultrasonic bath (Transsonic-700, 37 kHz, Germany) at 50 • C. The MPPE was centrifuged at 3,000 rpm for 10 min; the supernatant was obtained, and the residues were discarded. The solvent in the supernatant was evaporated using an R-200-Buchi-rotary evaporator (Switzerland), and the concentrated MPPE was obtained; The yield percentage of MPPE was evaluated using the following equation, the methanol-free extract was lyophilized and retained in water when the use (39).…”
Section: Preparation Of Plant Materialsmentioning
confidence: 99%